Cultivation Theory Analysis: The Cultural Impact of Chinese Drama Communication on Domestic Harmony - Geofakta Razali; Irwan Amar; Damayanti Masduki; Hermina Manhuruk; Yuliani Widianingsih (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This This study aims to analyze and test the application of George Gerbner 's Cultivation Theory in the context of the influence of Chinese Drama (C -Drama) on viewers' perceptions of Domestic Harmony . Along with the penetration of digital media and the globalization of entertainment, C-Drama has become a significant cultural phenomenon among Indonesian viewers. These shows often present narratives that emphasize traditional Chinese values, patriarchal family structures, specific gender roles, and ideal expectations or realistic conflicts in marriage. This study hypothesizes that long-term exposure to these narratives will influence viewers' perceptions of social reality, particularly regarding the norms and dynamics of household relationships. The research method used is quantitative with a survey approach . The research population is married adult viewers in urban areas who regularly and intensively watch C-Drama for at least two years (heavy viewers), as well as a control group ( light viewers ). Data were collected through a questionnaire that measures: (1) Exposure Level ; (2) Perception of Social Reality regarding the role of husband/wife, conflict resolution, and harmony standards; and (3) Support for the Main Principles in C-Drama. Data analysis was carried out using Binary Logistic Regression techniques and Spearman Correlation tests to compare differences in perception between heavy viewers and light viewers (differential cultivation effects). The results of the study indicate that there is a significant cultivation effect among heavy C-Drama viewers . Viewers with high exposure tend to have more idealistic or, conversely, more dramatic perceptions of conflict and gender roles in the household compared to light viewers. Specifically, heavy viewers show a higher tendency to internalize the values ​​of filial piety or unrealistic romantic expectations towards partners, which can potentially trigger mismatched expectations in the practice of household harmony. This study concludes that C-Drama narratives act as a "symbolic environment" that shapes viewers' views, requiring critical media literacy to distinguish fiction from social reality.